2015
DOI: 10.1007/s10549-015-3543-8
|View full text |Cite
|
Sign up to set email alerts
|

Imaging breast cancer morphology using probe-based confocal laser endomicroscopy: towards a real-time intraoperative imaging tool for cavity scanning

Abstract: Current techniques for assessing the adequacy of tumour excision during breast conserving surgery do not provide real-time direct cytopathological assessment of the internal cavity walls within the breast. This study investigates the ability of probe-based confocal laser endomicroscopy (pCLE), an emerging imaging tool, to image the morphology of neoplastic and non-neoplastic breast tissues, and determines the ability of histopathologists and surgeons to differentiate these images. Freshly excised tumour sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 49 publications
1
27
0
1
Order By: Relevance
“…The dataset is collected by a pre-clinical pCLE system (Cellvizio, Mauna Kea Technologies, Paris, France) as described in [11]. Breast tissue samples are obtained from 45 patients that are diagnosed with three main classes including normal, benign and and neoplastic.…”
Section: Dataset and Experimental Settingsmentioning
confidence: 99%
“…The dataset is collected by a pre-clinical pCLE system (Cellvizio, Mauna Kea Technologies, Paris, France) as described in [11]. Breast tissue samples are obtained from 45 patients that are diagnosed with three main classes including normal, benign and and neoplastic.…”
Section: Dataset and Experimental Settingsmentioning
confidence: 99%
“…A preliminary study on 71 ex-vivo breast tissue samples imaged with the Cellvizio pCLE system (Mauna Kea Technologies) demonstrated that cancerous and normal tissue could be differentiated by histopathologists with an accuracy of 94%. 10 This study used topically applied acriflavine, excited at 488 nm, which stains cell nuclei and enables high contrast imaging of tissue morphology. However, this is not currently an attractive option for in-vivo imaging due to the lack of regulatory approval and suggested risks of mutagenicity.…”
mentioning
confidence: 99%
“…The high frame rate enables image mosaics to be assembled more readily, 21 which, as discussed in Ref. 10, is important for allowing features to be identified with confidence.…”
mentioning
confidence: 99%
See 2 more Smart Citations